2012
DOI: 10.1038/emboj.2012.214
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Rif1 is a key regulator of the replication-timing programme in mammalian cells

Abstract: The eukaryotic genome is replicated according to a specific spatio-temporal programme. However, little is known about both its molecular control and biological significance. Here, we identify mouse Rif1 as a key player in the regulation of DNA replication timing. We show that Rif1 deficiency in primary cells results in an unprecedented global alteration of the temporal order of replication. This effect takes place already in the first S-phase after Rif1 deletion and is neither accompanied by alterations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
308
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(339 citation statements)
references
References 62 publications
28
308
2
1
Order By: Relevance
“…Recent studies revealed that Rif1 is a regulator of both DNA replication timing (14,15) and pathway choice during DSB repair (8 -12). However, the identification of Rif1 molecular function has been limited by challenges encountered while producing recombinant material for in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies revealed that Rif1 is a regulator of both DNA replication timing (14,15) and pathway choice during DSB repair (8 -12). However, the identification of Rif1 molecular function has been limited by challenges encountered while producing recombinant material for in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies clearly indicate that this protein plays an important function in multiple aspects of DNA metabolism. Furthermore, in mammalian cells, Rif1 is found in the insoluble nuclear matrix fraction (14,15), where DNA replication factories and repair foci are organized (16,17). Because of this association with the insoluble nuclear fraction, it is technically challenging to address in vivo the questions of whether and how Rif1 binds DNA; similarly, it is also not possible to purify significant quantities of active material from the native source necessitating a recombinant approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 and 32). In yeast, due to loss of Rif1 both early-late and late-early switching of origin firing has been documented, and in mammalian cells even more dramatic defects in the replication program have been observed, such as fusing of distinct replication domains (33,34). Fostering of heterochromatin by the smallest subclones was also strongly dependent on Taz1 and Rif1 ( Fig.…”
Section: Ir -R + Ir -R δ S T a R 1 S T A R 2 S T A R 5 S T A R 4 ( Smentioning
confidence: 83%
“…RIF1 also plays important roles in DNA replication. RIF1 colocalizes with replication forks mostly at pericentromeric heterochromatin in mid-S phase and is required for the regulation of replication timing and the assembly of newly replicated heterochromatin [60,61]. Although RIF1 interacts directly with BLM [62], the localization of RIF1 on C-UFBs does not depend on BLM, and vice versa [56].…”
Section: Proteins That Recognize and Process Hr-ufbsmentioning
confidence: 99%